2006
DOI: 10.1111/j.1530-0277.2006.00205.x
|View full text |Cite
|
Sign up to set email alerts
|

Teenagers Are Right—Parents Do Not Know Much: An Analysis of Adolescent–Parent Agreement on Reports of Adolescent Substance Use, Abuse, and Dependence

Abstract: Whether for clinical or research purposes, the results emphasize the importance of directly assessing adolescents regarding alcohol and other substance use disorders. Furthermore, investigators should consider the specific disorder(s) being investigated and the ages of the children being studied when determining whether to include parent reports as part of study design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
1
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 39 publications
4
49
1
2
Order By: Relevance
“…We extended these fi ndings to include high-risk youths involved in public systems of care. Similar to previous studies, alcohol and marijuana were the most frequently used substances by youths, with half of youths having used them at least once in their lifetime, and parent-youth agreement was highest for marijuana use (Fisher et al, 2006;Langhinrichsen et al, 1990;McGillicuddy et al, 2007). Psychiatric research pointing to higher agreement among disorders with more observable behaviors (Achenbach et al, 1987) may explain the higher agreement for marijuana use, because the odors and residues associated with marijuana may be more evident to parents.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…We extended these fi ndings to include high-risk youths involved in public systems of care. Similar to previous studies, alcohol and marijuana were the most frequently used substances by youths, with half of youths having used them at least once in their lifetime, and parent-youth agreement was highest for marijuana use (Fisher et al, 2006;Langhinrichsen et al, 1990;McGillicuddy et al, 2007). Psychiatric research pointing to higher agreement among disorders with more observable behaviors (Achenbach et al, 1987) may explain the higher agreement for marijuana use, because the odors and residues associated with marijuana may be more evident to parents.…”
Section: Discussionsupporting
confidence: 79%
“…Cantwell and colleagues (1997) found that youths and parents had the lowest level of agreement when reporting alcohol abuse/dependence symptoms (κ = .19) and an average level of agreement about substance abuse/dependence (κ = .41) compared with other major psychiatric diagnostic categories assessed in this study (overall κ = .42). Fisher et al (2006) found comparable rates of agreement for alcohol abuse/dependence (κ = .37) and marijuana abuse/dependence (κ = .35), whereas O'Donnell et al (1998) found moderate rates of diagnostic agreement for alcohol abuse/dependence (κ = .44) and low agreement for drug abuse/dependence (κ = .29). Despite differing levels of agreement, most studies consistently fi nd greater levels of substance-related problems among youth reporters compared with their parents (Cantwell et al, 1997;Fisher et al, 2006;O'Donnell et al, 1998).…”
Section: Correspondence Between Parental and Youth Report Of Substancmentioning
confidence: 94%
See 2 more Smart Citations
“…Parents tend to be uninformed about their teen's alcohol use and related problems. 23 Blood and breath tests for alcohol yield positive results for only a few hours after consumption. Health care professionals can improve the validity of reports by assuring patients that their reports will be kept in confidence.…”
Section: Diagnosis Of Audsmentioning
confidence: 99%